Tumor Cells Develop Defined Cellular Phenotypes After 3D-Bioprinting in Different Bioinks - Schmidt, Sonja; Schmid, Rafael; Arkudas, Andreas; Kengelbach-Weigand, Annika; Boßerhoff, Anja Katrin (Cells, 2019)
Malignant melanoma is often used as a model tumor for the establishment of novel therapies. It is known that two-dimensional (2D) culture methods are not sufficient to elucidate the various processes during cancer development and progression. Therefore, it is of major interest to establish defined biofabricated three-dimensional (3D) models, which help to decipher complex cellular interactions. To get an impression of their printability and subsequent behavior, we printed fluorescently labeled melanoma cell lines with Matrigel and two different types of commercially available bioinks, without or with modification (RGD (Arginine-Glycine-Aspartate)-sequence/laminin-mixture) for increased cell-matrix communication. In general, we demonstrated the printability of melanoma cells in all tested biomaterials and survival of the printed cells throughout 14 days of cultivation. Melanoma cell lines revealed specific differential behavior in the respective inks. Whereas in Matrigel, the cells were able to spread, proliferate and form dense networks throughout the construct, the cells showed no proliferation at all in alginate-based bioink. In gelatin methacrylate-based bioink, the cells proliferated in clusters. Surprisingly, the modifications of the bioinks with RGD or the laminin blend did not affect the analyzed cellular behavior. Our results underline the importance of precisely adapting extracellular matrices to individual requirements of specific 3D bioprinting applications.
CRIS-Team WoS Importer:2019-11-29